1993
DOI: 10.1542/peds.91.6.1166
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Positive Throat Cultures for Group A Streptococci After Initiation of Antibiotic Therapy

Abstract: Objective. To determine if it is appropriate to recommend that patients with group A β-hemolytic streptococcal pharyngitis, who are clinically well by the morning after starting antibiotic treatment, can return to school or day care, or if they should wait until they have completed 24 hours of antibiotics as recommended by the American Academy of Pediatrics Committee on Infectious Diseases. Methods. We examined the duration of positivity of the throat culture after antibiotics were begun as a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 0 publications
4
11
0
1
Order By: Relevance
“…Five studies reported IM penicillin therapy; results were consistent with our findings for antibiotics overall[28,39,54,59,64]. Snellman et al found 1/15 (6.7%) children were culture-positive at 24 hours following single dose benzathine penicillin[28].…”
supporting
confidence: 85%
See 4 more Smart Citations
“…Five studies reported IM penicillin therapy; results were consistent with our findings for antibiotics overall[28,39,54,59,64]. Snellman et al found 1/15 (6.7%) children were culture-positive at 24 hours following single dose benzathine penicillin[28].…”
supporting
confidence: 85%
“…Five studies reported IM penicillin therapy; results were consistent with our findings for antibiotics overall[28,39,54,59,64]. Snellman et al found 1/15 (6.7%) children were culture-positive at 24 hours following single dose benzathine penicillin[28]. Lester et al reported no positive cases at day 5 among 126 patients treated either with Benzathine penicillin or combined Benzathine Penicillin/Procaine Penicillin G[39].…”
supporting
confidence: 82%
See 3 more Smart Citations